Joint remembering in collaborative design: a multimodal approach in the case of a video design studio. Issue 4 (1st October 2016) - Bietti, Lucas M.; Baker, Michael J.; Détienne, Françoise
Abstract: The aim of this paper is to explore the role of joint remembering in collaborative design. Joint remembering sequences are identified on the basis of questions that act as triggers to specific interactive sequences. The sequences are situated in the ongoing collaborative design process, and empirical evidence is provided that illustrates how the interweaving of verbal, bodily, social and material resources supports joint remembering. Three examples of joint remembering sequences in co-design are analysed from a corpus of interactions (45+ hours of audio and video recording), collected during an observational study of a team of four 3D designers working on a TV commercial. This study suggests that questions acting as reminders foster the formation of multimodal remembering sequences (MRSs) that connect multiple timescales over the duration of co-design projects. In the corpus under study, MRSs enable designers to plan future actions and make decisions on the fly.